الترجمة بوصفها أداة لتدريس اللغة العربية : دراسة تجريبية وتحليلية - Asiah binti Abas (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2015)
This paper starts with the assumption that translation -when applied correctly- can be used as a means of teaching foreign language. The idea –teaching foreign language via translation- raises criticism and condemnation due to the misunderstanding that it is similar to traditional method of teaching specifically grammar translation method. Therefore, the researcher tries to investigate the role of translation and its potential contributions to the field of teaching Arabic as a second language. To identify the results, the researcher analyzed learners' reaction and acceptance to the use of translation in the classroom through descriptive and analytical methods on 53 undergraduate students of Arabic Department, International Islamic University Malaysia. The analysis was done by analyzing their translation works and answers in their questionnaires. In general, results of the study show a positive reception of translation, more specifically, it has been proven that translation helped learners to improve their understanding of Arabic language and advance their proficiency level. The efficiency and benefit of translation not was only found in the four main languages skills (listening, speaking, reading and writing), butalso in other language areas such as vocabulary, grammar, morphology, writing style and others. It seems that common mistakes committed by learners either at word level, word order or writing style can be overcome with the help of translation. At the end of the study, some recommendations on how to use translation correctly and effectively were given.